Nordwestspanien. Der Nordwesten der Iberischen Halbinsel als integrative Kontaktzone indigener und römischer Bevölkerung. Die Arbeiten des Jahres 2019 - Mossong, Isabelle (e-Forschungsberichte des DAI, 2020)
The aim of this habilitation project in Ancient History started in 2016 is to examine the reciprocal interchange between Roman and indigenous habits and their influence on the local society in the north-western territory of the Iberian Peninsula. It is set in a time span extending from the late 1st century B.C., when the Romans conquered the last remaining region in Hispania outside of their power, through Late Antiquity. The primary objective of the year 2019 was to analyze the impact of local and Roman customs on the funerary habits, by focusing on the epigraphical testimonies from the conventus Asturum.